Creating the 'New Europe' through Postal Services Setting Postal Standards during World War II - Proschmann, Sabrina (Historische Dimensionen Europäischer Integration, 2022)
This thesis analyses the European Postal and Telecommunications Union, founded in Vienna in October 1942 under the leadership of the Axis powers. Both technocratic internationalism and the propaganda term 'New Europe' found points of contact there. The German postal administration authority used the union to extend Germany's domestic postal system to intra-European postal services and to ensure German supremacy in the new postal Europe. After the war, a respective regional postal organisation was founded in both the Eastern and Western European blocs in the late 1950s. The content of the standardisation envisaged through this measure did not differ much in both blocs, but the way in which the standardisation was carried out did.